Appearance-based obstacle detection using monocular color vision - Fernandez, Ryan P. (2005)
In this research a monocular color vision-based mobile robot platform is developed that is capable of detecting and avoiding obstacles. The robot vision system for detecting obstacles is appearance-based and combines the edge and the region information of the captured image to generate a single obstacle image map representing the nearest obstacles. The vision system implements a two-class segmentation scheme done in the HSV color space to determine traversable and non-traversable areas in the input image. In the test conducted, the mobile robot successfully avoids obstacles in an office environment through its programmed reactive behaviour.
Thesis (B.S. Computer Engineering)--University of the Philippines, Diliman.
Keywords: Robot vision; Mobile robots; Obstacle detector; Monocular color vision